Emulsifiers in the poultry industry. Issue 3 (1st August 2017) - SIYAL, F.A.; BABAZADEH, D.; WANG, C.; ARAIN, M.A.; SAEED, M.; AYASAN, T.; ZHANG, L.; WANG, T.
Abstract : Emulsifiers are used in poultry nutrition for improving poultry performance, digestibility of the nutrients, especially fats, and include soy-lecithin, milk derived casein, lysophatidylcholine or lysolecithin (lecithin), bile salt, glycerol polyethylene glycol ricinoleate (E 484), and sodium stearoyl-2-lactylate (SSL) etc. The efficacy of emulsifying agents can be used with different vegetable oils and various levels of metabolisable energy (ME). The literature shows that the selection of various natural and synthetic sources of emulsifiers should be on the basis of their hydrophilic-lipophilic balance (HLB). There are new directions regarding exogenous and natural emulsifying agents, their blends in poultry diet and importance of in vitro studies. The following review includes comparisons of emulsifying agents and their impact on performance in poultry.